Immunotherapy Targeting Tumor-Associated Macrophages - Liu, Yafei; Wang, Rongsi (Frontiers in Medicine, 2020)
Macrophages are phagocytic cells that play a broad role in maintaining body homeostasis and defense against foreign pathogens. Whereas, tumor-associated macrophages (TAMs) support tumor growth and metastasis by promoting cancer cell proliferation and invasion, immunosuppression, and angiogenesis, which is closely related to the poor prognosis in almost all solid tumors. Hence, deep insight knowledge into TAMs can provide an opportunity to discover more effective strategies for cancer therapeutic. So far, a large number of therapeutic agents targeting TAMs are in clinical trials. In this review, we would introduce reader an extensive overview about macrophages and macrophage-targeting agents.